2001
DOI: 10.1046/j.1365-2583.2001.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative linkage map development and identification of an autosomal locus for insensitive acetylcholinesterase‐mediated insecticide resistance in Culex tritaeniorhynchus

Abstract: A comparative linkage map for Culex tritaeniorhynchus was constructed based on restriction fragment length polymorphism markers using cDNAs from Aedes aegypti. Linear orders of marker loci in Cx. tritaeniorhynchus were identical to Culex pipiens wherein chromosomes 2 and 3 reflect whole-arm rearrangements compared to A. aegypti. However, the sex determination locus in Cx. tritaeniorhynchus maps to chromosome 3, in contrast to Cx. pipiens and Ae. aegypti where it is located on chromosome 1. Our results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 40 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Subsequently, amino acid substitutions were identified in the Cyclorrhapha fly species, Musca domestica (Huang et al, 1997;Kozaki et al, 2001;Walsh et al, 2001), Lucilia cuprina (Chen et al, 2001), and Bactrocera oleae (Vontas et al, 2002); however, no insecticide insensitivity-attributable mutation was found in Ace orthologues of the resistant strains of other insect species such as Culex pipiens (Malcolm et al, 1998), Cx. tritaeniorhynchus (Mori et al, 2001), Nephotettix cincticeps (Tomita et al, 2000) and Plutella xylostella (Ni et al, 2003). Recently, another class of AChE genes, paralogous to Ace, has been reported from the green bug, Schizaphis graminum (Gao et al, 2002) and a mosquito, Anopheles gambiae (Weill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, amino acid substitutions were identified in the Cyclorrhapha fly species, Musca domestica (Huang et al, 1997;Kozaki et al, 2001;Walsh et al, 2001), Lucilia cuprina (Chen et al, 2001), and Bactrocera oleae (Vontas et al, 2002); however, no insecticide insensitivity-attributable mutation was found in Ace orthologues of the resistant strains of other insect species such as Culex pipiens (Malcolm et al, 1998), Cx. tritaeniorhynchus (Mori et al, 2001), Nephotettix cincticeps (Tomita et al, 2000) and Plutella xylostella (Ni et al, 2003). Recently, another class of AChE genes, paralogous to Ace, has been reported from the green bug, Schizaphis graminum (Gao et al, 2002) and a mosquito, Anopheles gambiae (Weill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Two lines of evidence support this conclusion: (i) absence of non-synonymous point mutations between susceptible and resistant strains (Aphis gossypii, Nephotettix cincticeps, Boophilus microplus (Baxter & Barker 1998;Hernandez et al 1999;Menozzi 2000;Tomita et al 2000)), (ii) independent segregation in crosses between the cloned ace gene and resistance (Culex pipiens (Malcolm et al 1998) and Cx. tritaeniorynchus (Mori et al 2001)). Involvement of ace genes in resistance in other arthropods is not known, either because insensitive AChE has not been described in some species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…pipiens, with distinct catalytic properties (Bourguet et al 1996). Although two ace genes have been identified in Arachnidae (Baxter & Barker 1998;Hernandez et al 1999), intensive searches for a second ace gene in several insect species has remained unsuccessful (Severson et al 1997;Menozzi 2000;Mori et al 2001;Tomita et al 2000; see however Gao et al 2002). This indicates that if a second ace gene exists in insects, its divergence from the first one complicates the cloning by homology with the first gene by classical PCR and Southern blotting techniques.…”
Section: Introductionmentioning
confidence: 99%
“…reflect whole chromosome arm translocations that involve a breakpoint between the LF106 and LF386 loci when compared to Ae. aegypti (Mori et al, 1999(Mori et al, ,2001). The Ace1 homolog in Cx.…”
Section: Ace1 Genome Locationmentioning
confidence: 99%
“…conferring resistance were unsuccessful in Orthorrhapha dipterans, including the mosquitoes Culex pipiens (Malcolm et al, 1998) and Culex tritaeniorhynchus (Mori et al, 2001), despite documentation of insensitive AChE-mediated resistance in both species. Of note, the resistance phenotype mapped to a different genome location than the Ace locus, suggesting the existence of an independent molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%